2008
DOI: 10.1016/j.cellbi.2008.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium toxicity in cultured tomato cells—Role of ethylene, proteases and oxidative stress in cell death signaling

Abstract: Our aim was to investigate the ability of cadmium to induce programmed cell death in tomato suspension cells and to determine the involvement of proteolysis, oxidative stress and ethylene. Tomato suspension cells were exposed to treatments with CdSO(4) and cell death was calculated after fluorescein diacetate staining of the living cells. Ethylene was measured in a flow-through system using a laser-driven photo acoustic detector; hydrogen peroxide was determined by chemiluminescence in a ferricyanide-catalysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 71 publications
4
31
0
3
Order By: Relevance
“…Fojtova and Kovarik (2000) reported that 50 M CdSO 4 induced a rapid decrease in cell viability and distinct changes in cell morphology and DNA integrity in tobacco suspension cultures. Similar results have been reported in tomato suspension cells (Iakimova et al 2008). In this study, chromatin condensation and DNA strand breaks, which are considered the hallmarks of PCD, were observed in BY-2 suspension cultures treated with 150 M CdCl 2 (Figs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Fojtova and Kovarik (2000) reported that 50 M CdSO 4 induced a rapid decrease in cell viability and distinct changes in cell morphology and DNA integrity in tobacco suspension cultures. Similar results have been reported in tomato suspension cells (Iakimova et al 2008). In this study, chromatin condensation and DNA strand breaks, which are considered the hallmarks of PCD, were observed in BY-2 suspension cultures treated with 150 M CdCl 2 (Figs.…”
Section: Discussionsupporting
confidence: 77%
“…Cd 2+ also induced PCD or apoptosis in plant tissues, such as onion root tips (Behboodi and Samadi 2004). Recently, Iakimova et al (2008) reported that CdSO 4 induced PCD by exhibiting caspase-like proteases, inducing morphological and biochemical similarities to hypersensitive responses in tomato suspension cells. Similarly, exposure of the Arabidopsis suspension cultures to CdCl 2 stress led to a senescence-like process that eventually ended with PCD (De Michele et al 2009).…”
mentioning
confidence: 99%
“…Iakimova et al (2008) reported that the combination of ethylene and Cd treatments to tomato (Solanum lycopersicum) suspension cells resulted in increased cell death, which could be rescued by adding AVG (Fig. 1).…”
Section: Effects Of Ethylene Modulators On Ethylene Biosynthesis Undementioning
confidence: 99%
“…Several studies have proved that the application of ethylene biosynthesis modulators adjusted endogenous stress-induced ethylene content to an optimized level and, consequently, resulted in beneficial effects in plants treated with Ni and Zn Khan and Khan, 2014), Cd (Iakimova et al, 2008;Sun et al, 2010;Chmielowska-Bąk et al, 2014), or Al (Sun et al, 2010). Additionally, S application has proved to be effective in the alleviation of Cd stress, which was related to the reduction of undesirable stress-induced ethylene production in mustard, suggesting that S might be used to optimize the ethylene level for developing HM stress-tolerant cultivars as well (Asgher et al, 2014;Khan et al, 2015a).…”
Section: Improvement Of Plant Tolerance To Hm: An Approach Of Modifyimentioning
confidence: 99%
“…Bununla birlikte, ağır metal toleransının hormonal düzenlenme mekanizması ile ilgili bilgiler sınırlıdır. Kadmiyumun Cd stres cevaplarının düzenlenmesinde, poliaminler ve etilen hormonlarının fonksiyon gördüğü bildirilmiştir (Groppa et al 2001;Iakimova et al 2008). Birçok proteomik çalışmada, etilen ve poliamin biyosentezinde rol alan S-adenozil-Lmetiyonin (SAM) sentetaz proteininin miktarında önemli artış belirlenmiştir (Aloui et al 2009;Sharmin et al 2012;Wu et al 2013).…”
Section: Sinyal İletim Mekanizması Ve Sekonder Metabolizma Ile İlişkiunclassified